2009
DOI: 10.1007/978-90-481-3471-7_7
|View full text |Cite
|
Sign up to set email alerts
|

Function of TopBP1 in Genome Stability

Abstract: Human DNA topoisomerase IIbeta-binding protein 1 (TopBP1) and its orthologues in other organisms are proteins consisting of multiple BRCT modules that have acquired several functions during evolution. These proteins execute their tasks by interacting with a great variety of proteins involved in nuclear processes. TopBP1 is an essential protein that has numerous roles in the maintenance of the genomic integrity. In particular, it is required for the activation of ATM and Rad3-related (ATR), a vital regulator of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 93 publications
1
32
0
Order By: Relevance
“…The PCNA-like clamp 9-1-1 complex (Rad9-Rad1-Hus1) is recruited preferentially to the 5′-primed ssDNA/dsDNA junction by RPA and the clamp loader Rad17-RFC complex [102105]. The ATR-ATRIP complex and 9-1-1 complexes are recruited to RPA-ssDNA independently and are bridged by the multiple-function protein TopBP1 (Topoisomerase IIβ binding protein 1) [106110]. TopBP1 contains nine BRCT domains and is required for DNA replication initiation via the recruitment of CDC45 [111, 112].…”
Section: Dna Damage Response Pathways In Oxidative Stressmentioning
confidence: 99%
“…The PCNA-like clamp 9-1-1 complex (Rad9-Rad1-Hus1) is recruited preferentially to the 5′-primed ssDNA/dsDNA junction by RPA and the clamp loader Rad17-RFC complex [102105]. The ATR-ATRIP complex and 9-1-1 complexes are recruited to RPA-ssDNA independently and are bridged by the multiple-function protein TopBP1 (Topoisomerase IIβ binding protein 1) [106110]. TopBP1 contains nine BRCT domains and is required for DNA replication initiation via the recruitment of CDC45 [111, 112].…”
Section: Dna Damage Response Pathways In Oxidative Stressmentioning
confidence: 99%
“…Additionally, another repressor domain exists on the C terminus of the activation domain, which requires amino acids 586 -675. TopBP1 protein exerts its function in the nucleus and the carboxyl-terminal region of TopBP1 contains two putative nuclear localization signals (Going et al, 2007;Liu et al, 2003;Sokka et al, 2010). Liu et al (2003) showed that deletion of the BRCT7-8 and NLS region of TopBP1 induces cytoplasmic localization of the protein.…”
Section: Fig 2 Topbp1 Functional Domains and Sites Of Interacting Pmentioning
confidence: 99%
“…The process is catalyzed by the poly(ADP-ribose) polymerase (PARP) family of proteins. The best known of these proteins is PARP1 which is implicated in transcription, chromatin remodeling, apoptosis and DNA repair (Sokka et al, 2010;Woodhouse & Dainov, 2008). TopBP1 and PARP-1 interact both in vitro and in vivo.…”
Section: Topbp1 As Multifunctional Proteinmentioning
confidence: 99%
See 2 more Smart Citations